The secret of secrets : a novel - Brown, Dan, 1964- (New York : Doubleday, 2025)
"Robert Langdon, esteemed professor of symbology, travels to Prague to attend a groundbreaking lecture by Katherine Solomon--a prominent noetic scientist with whom he has recently begun a relationship. Katherine is on the verge of publishing an explosive book that contains startling discoveries about the nature of human consciousness and threatens to disrupt centuries of established belief. But a brutal murder catapults the trip into chaos, and Katherine suddenly disappears along with her manuscript. Langdon finds himself targeted by a powerful organization and hunted by a chilling assailant sprung from Prague's most ancient mythology. As the plot expands into London and New York, Langdon desperately searches for Katherine . . . and for answers. In a thrilling race through the dual worlds of futuristic science and mystical lore, he uncovers a shocking truth about a secret project that will forever change the way we think about the human mind."--Dust jacket flap.
Maps on endpapers.
Donated by Farhana Zahir, Assistant Professor, BRAC Business School, BRAC University
Keywords: Langdon, Robert -- (Fictitious character) -- Fiction; College teachers -- Fiction; Women scientists -- Fiction; Symbolism -- Fiction; Consciousness -- Research -- Fiction; Mind and body -- Research -- Fiction; Missing persons -- Fiction; Mysticism -- Fiction; FICTION / Thrillers / Suspense; FICTION / Action & Adventure; FICTION / Thrillers / Technological; Teachers -- Fiction; Women scientists -- Fiction; Symbolism -- Fiction; Consciousness -- Fiction; Mind and body -- Fiction; Missing persons -- Fiction; Mysticism -- Fiction; Thrillers (Fiction); Action and adventure fiction; Novels